1998
DOI: 10.1063/1.120862
|View full text |Cite
|
Sign up to set email alerts
|

Schottky barrier photodetectors based on AlGaN

Abstract: We report solar-blind AlxGa1−xN photovoltaic detectors with cutoff wavelengths as short as 290 nm. Mesa geometry devices of different active areas are fabricated and characterized for spectral responsitivity, speed, and noise performance. The responsivity of the devices near the cutoff wavelength is 0.07 A/W. The detector noise is found to be 1/f limited, with a noise equivalent power of 6.6×10−9 W over the total response bandwidth of 100 kHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
72
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(73 citation statements)
references
References 7 publications
1
72
0
Order By: Relevance
“…In addition, AlGaN-based solar-blind detectors can operate under harsh conditions due to their wide bandgap and robust material properties [2]. Several research groups have demonstrated high-performance solar-blind photodetectors using Al Ga N material system [3]- [12].…”
mentioning
confidence: 99%
“…In addition, AlGaN-based solar-blind detectors can operate under harsh conditions due to their wide bandgap and robust material properties [2]. Several research groups have demonstrated high-performance solar-blind photodetectors using Al Ga N material system [3]- [12].…”
mentioning
confidence: 99%
“…6 Fig . 5 illustrates the plot of the responsivity versus dark current for the state-of-the-art solar blind (230-290 nm) UV detectors reported [4][5][6]8,[10][11]16,[30][31][32][33][34][35][36][37] for the devices based on Al x Ga 1-x N as well as on β-Ga 2 O 3 . The detectors reported in this work have excellent responsivity while maintaining a very low dark current for 230-240 nm range.…”
mentioning
confidence: 99%
“…In recent years, various types of AlGaN-based photodetectors have been reported, such as Schottky, pin, and MSM [1][2][3]. Previously, the authors reported on the RuO 2 Schottky contact properties [4] and a RuO 2 /GaN photodetector [5], which exhibited a responsivity and UV/visible rejection ratio of 0.23 A/W at 330 nm and 3 Â 10…”
mentioning
confidence: 99%